Воєнні втрати аграрного сектору: моніторинг, організація обліку та звітність - Єрмолаєва Марина; Jermolájeva M.; Yermolaieva M.; Луценко Дмитро; Lucenko D.; Lutsenko D. (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Резюме. Повномасштабне вторгнення РФ призвело до суттєвого знищення інфраструктури аграрного сектору України, втрат сільськогосподарської техніки, знищення урожаю, мінування територій, порушення виробничо-логістичних ланцюгів, що суттєво впливає на продовольчу безпеку як України, так і світу. В умовах викликів, спричинених бойовими діями, особливої актуальності набуває потреба в системному обліку та моніторингу втрат аграрного виробництва з метою їх подальшого відшкодування, формування обґрунтованої статистики, стратегічного планування та забезпечення прозорості в управлінні державними і донорськими ресурсами.У статті розглянуто теоретико-методичні засади організації моніторингу й обліку воєнних втрат аграрних підприємств, запропоновано підходи до класифікації втрат на прямі, непрямі та потенційні, виокремлено їх особливості в умовах повномасштабної війни. Проаналізовано існуючі прогалини у чинному законодавстві та нормативному забезпеченні щодо відображення збитків, спричинених надзвичайними подіями воєнного характеру. Наголошено на відсутності єдиних механізмів документального підтвердження та оцінки втрат, що створює труднощі для підприємств у процесі звернення за компенсаціями.Акцентовано на доцільності запровадження в облікову практику аграрних підприємств окремих субрахунків для обліку втрат, пов’язаних із війною, а також на потребі уніфікації первинних документів, актів обстеження пошкоджених активів, фотофіксації, висновків експертів тощо. Обґрунтовано необхідність створення державної платформи або реєстру фіксації втрат, який би забезпечував достовірність і верифікацію даних.Також розглянуто перспективи цифровізації процесів обліку і моніторингу втрат через впровадження електронних реєстрів, облікових модулів та аналітичних панелей, що дозволить оперативно відслідковувати ситуацію, формувати звітність і підвищувати ефективність управлінських рішень.

Az Orosz Föderáció teljes körű inváziója az ukrán agrárszektor infrastruktúrájának jelentős megsemmisüléséhez, mezőgazdasági gépek elvesztéséhez, termés megsemmisüléséhez, területek aknázásához, termelési és logisztikai láncok megszakításához vezetett, ami jelentősen befolyásolja mind Ukrajna, mind a világ élelmezésbiztonságát. A harci cselekmények okozta kihívások közepette különösen fontosá válik az agrártermelés veszteségeinek szisztematikus nyilvántartása és nyomon követése a későbbi kártérítés, a megalapozott statisztikák összeállítása, a stratégiai tervezés és az állami és donorforrások átlátható kezelése érdekében.A cikkben a mezőgazdasági vállalkozások háborús veszteségeinek nyomon követésénekés nyilvántartásának szervezésének elméleti és módszertani alapjait vizsgáljuk, megközelítéseket javaslunk a veszteségek közvetlen, közvetett és potenciális osztályozására, és kiemeljük azok sajátosságait teljes körű háború körülményei között. A cikk elemzi a hatályos jogszabályokban és a szabályozásban fennálló hiányosságokat a háborús jellegű rendkívüli események által okozott károk tükrözése tekintetében. Kiemelésre került, hogy hiányoznak az egységes mechanizmusok a veszteségek dokumentált igazolására és értékelésére, ami jelentős nehézségeket okoz a vállalkozások számára a kártérítési igények benyújtása soránHangsúlyozva van az agrárvállalkozások számviteli gyakorlatában a háborúval kapcsolatos veszteségek nyilvántartására szolgáló külön alszámlák bevezetésének célszerűsége, valamint az elsődleges dokumentumok, a sérült eszközök felmérési jegyzőkönyvei, fényképes dokumentáció, szakértői vélemények stb. egységesítésének szükségessége. Alaposan megindokolták egy állami platform vagy veszteségek nyilvántartásának létrehozását, amely biztosítaná az adatok hitelességét és ellenőrzését.Továbbá áttekintésre kerültek a veszteségek nyilvántartási és monitorozási folyamatainek digitalizációs lehetőségei, különös tekintettel az elektronikus nyilvántartások, számviteli modulok és analitikai panelek bevezetésére. Ez lehetővé teszi a helyzet operatív nyomon követését, a jelentések előállítását, valamint a vezetői döntések hatékonyságának növelését.

Abstract. The military aggression of the Russian Federation against Ukraine has led tolarge-scale destruction of the material base of the agricultural sector, the loss of agricultural machinery, destruction of crops, mining of land, and disruption of production and logistics chains. These consequences have significantly affectedfood security both in Ukraine and globally. Under the current challenges caused by hostilities, the need for systematic accounting and monitoring of agricultural production losses becomes especially urgent. Such monitoring is essential for further compensation, development of reliablestatistics, strategic planning, and ensuring transparency in the management of state and donor resources.The article explores the theoretical and methodological foundations of organizing the monitoring and accounting of war-related losses in agricultural enterprises. It proposes approaches to classifying losses into direct, indirect, and potential categories and highlights their specific features under conditions of full-scale warfare. The authors analyze the existing gaps in current legislation and regulatory frameworks concerning the recognitionof losses caused by emergency events of a military nature. Particular attention is paidto the absence of unified mechanisms for the documentation and assessment of losses, which complicates the process of claiming compensation by affected enterprises. The study emphasizes the importance of introducing separate sub-accounts into the accounting practices of agricultural enterprises for war-related losses, as well as the need to standardize primary documentation, damage assessment reports, photographic evidence, and expert conclusions. The necessity of creating a state platform or registry for recording losses is substantiated, as it would ensure the reliability and verification of the collected data.Additionally, the article examines the prospects for digitalizing the processes of accounting and monitoring of losses through the implementation of electronic registries, accounting modules, and analytical dashboards. This would allow real-time tracking, reporting, and improved efficiency of managerial decision-making.
A mezőgazdasági szektor háborús veszteségei: monitoring, számvitel szervezése és jelentéstétel
War Losses of the Agricultural Sector: Monitoring, Accounting Organization, and Reporting
Весь випуск: https://aab-economics.kmf.uz.ua/aabe/issue/view/11
Keywords: Воєнні втрати; моніторинг втрат; облік збитків; знищене майно; документування втрат